2007
DOI: 10.1016/j.epsl.2007.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced transformation of olivine to a new metastable (Mg,Fe)2SiO4 polymorph in Martian meteorites

Abstract: Shock-induced transformation of olivine to a new metastable (M g, F e) 2 SiO 4 polymorph in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
4
42
0
Order By: Relevance
“…Peak at 755 cm -1 : This peak was described both in the experimentally shocked and in natural samples (Durben et al 1993;Gillet et al 2005;van de Moortéle et al 2007). These authors suggested that this peak may be associated with the SiO 5 and SiO 6 molecules as "defects within the olivine structure" (Durben et al 1993;van de Moortéle et al 2007).…”
Section: Brown and Colorless Meteoritic Olivinementioning
confidence: 91%
See 4 more Smart Citations
“…Peak at 755 cm -1 : This peak was described both in the experimentally shocked and in natural samples (Durben et al 1993;Gillet et al 2005;van de Moortéle et al 2007). These authors suggested that this peak may be associated with the SiO 5 and SiO 6 molecules as "defects within the olivine structure" (Durben et al 1993;van de Moortéle et al 2007).…”
Section: Brown and Colorless Meteoritic Olivinementioning
confidence: 91%
“…These authors suggested that this peak may be associated with the SiO 5 and SiO 6 molecules as "defects within the olivine structure" (Durben et al 1993;van de Moortéle et al 2007). However, alternatively, Gillet et al (2005) suggested that the peak near at 750 cm -1 might be attributed to the presence of Si-O-Si bridges characteristic of wadsleyite.…”
Section: Brown and Colorless Meteoritic Olivinementioning
confidence: 99%
See 3 more Smart Citations